COVID-19 Testing in Schools: Perspectives of School Administrators, Teachers, Parents, and Students in Southern California. Issue 2 (March 2023) - Unger, Jennifer B.; Soto, Daniel; Lee, Ryan; Deva, Sohini; Shanker, Kush; Sood, Neeraj
Background: School-based COVID-19 testing is a potential strategy to facilitate the safe reopening of schools that have been closed due to the pandemic. This qualitative study assessed attitudes toward this strategy among four groups of stakeholders: school administrators, teachers, parents, and high school students. Methods: Focus groups and interviews were conducted in Los Angeles from December 2020 to January 2021 when schools were closed due to the high level of COVID transmission in the community. Results: Findings indicated similarities and differences in attitudes toward in-school COVID-19 testing. All groups agreed that frequent in-school COVID-19 testing could increase the actual safety and perceived safety of the school environment. School administrators expressed pessimism about the financial cost and logistics of implementing a testing program. Parents supported frequent testing but expressed concerns about physical discomfort and stigma for students who test positive. Teachers and parents noted that testing would prevent parents from sending sick children to school. Students were in favor of testing because it would allow them to return to in-person school after a difficult year of online learning. Conclusion: In-school COVID-19 testing could be a useful component of school reopening plans and will be accepted by stakeholders if logistical and financial barriers can be surmounted and stigma from positive results can be minimized.